Role of Police in Handling the Criminal Act of Child Sexual Abuse in Gorontalo City - Febywidyanti Rahman; Nopiana Mozin; Sastro M. Wantu (Universitas Muhammadiyah Palu, 2025)
This study aimed to understand how the police play a role in addressing criminal acts of sexual abuse against minors and to identify the factors that contribute to the occurrence of such crimes. This research employed a juridical empirical approach, which merges legal methods with empirical data from field studies involving the police, case documentation, literature reviews, and relevant legal materials. The study findings indicated that the police's role in handling child sexual abuse includes preventive, preemptive, repressive, and restorative aspects. In the preventive and preemptive aspects, the police conduct legal counseling, child protection campaigns, and cooperate with schools and communities to provide awareness about the dangers of sexual violence. In the repressive aspect, the police conduct investigations and legal actions against perpetrators based on applicable laws and regulations, such as the Indonesian Criminal Code (KUHP) and Law No. 1 of 2023 on the Indonesian Criminal Code. The restorative role is manifested through victim assistance and psychological and social recovery for children who are victims.